2020
DOI: 10.1123/jsr.2018-0346
|View full text |Cite
|
Sign up to set email alerts
|

Does an Accelerated Program Give Equivalent Results in Both Elite Athletes and Nonathletes?

Abstract: Context: Although many researchers have investigated the functional outcomes of different accelerated rehabilitation programs after anterior cruciate ligament reconstruction (ACLR), the functional results of the same accelerated rehabilitation program following ACLR applied for both elite athletes and nonathletes have not yet been investigated. Objective: To examine the effects of the same accelerated anterior cruciate ligament rehabilitation program on pain and functionality of elite athletes and nonathletes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…The 2 studies with very low quality were downgraded owing to risk of bias, imprecision, and indirectness of results (Table 3). There were 7 noncomparative studies 5,7-9,13,19,33 and 7 comparative studies 18,21,25,32,37,41,49 assessed with the MINORS. The noncomparative studies had a median score of 9 of 16 (range, [5][6][7][8][9][10][11], indicating that they were of fair quality.…”
Section: Quality Appraisalmentioning
confidence: 99%
See 3 more Smart Citations
“…The 2 studies with very low quality were downgraded owing to risk of bias, imprecision, and indirectness of results (Table 3). There were 7 noncomparative studies 5,7-9,13,19,33 and 7 comparative studies 18,21,25,32,37,41,49 assessed with the MINORS. The noncomparative studies had a median score of 9 of 16 (range, [5][6][7][8][9][10][11], indicating that they were of fair quality.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…c Assessment after rating the evidence using GRADE (high, moderate, low, very low). 18 30 ACLR 6 wk after ACLR Mainwaring (2010) 37 7 ACL injury 30 d Baranoff (2015) 5 44 ACLR 6 mo after ACLR Langford (2009) 32 87 ACLR 6 mo after ACLR Oztekin (2008) 41 30 ACL injury 3 wk after ACLR Filbay (2017) 19 162 ACLR 5-20 y after ACLR Tripp (2003) 49 20 ACLR N/A C ¸elebi (2015) 13 38 ACLR 6 wk after ACLR Brewer (2003) 7 91 ACL injury 24 mo after ACLR Brewer (2013) 8 91 ACL injury 24 mo after ACLR Anxiety Oztekin (2008) 41 30 ACL injury 3 wk after ACLR Hemsley (2010) 25 22 6 wk after ACLR N/A Tripp (2003) 49 20 ACLR N/A C ¸elebi (2015) 13 38 ACLR 6 wk after ACLR Filbay (2017) 19 162 5-20 years after ACLR N/A Lepley (2018) 33 20 6 mo after ACLR Brewer (2000) 9 61 ACL injury N/A Brewer (2003) 7 91 ACL injury 24 mo after ACLR Brewer (2013) 8 91 ACL injury 24 mo after ACLR Qualitative Carson (2012) 11 5 6-12 mo after ACLR Carson (2008) 12 1 Interview every 2 wk after ACLR a ACL, anterior cruciate ligament; ACLR, anterior cruciate ligament reconstruction; N/A: not applicable (due to the lack of reported data, or the use of an outcome measurement for which cut-offs were not found in the literature).…”
Section: Study (Year)mentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the accelerated protocol to conservative patients in both elite athletes and nonathletes, Feyzio glu et al 19 found that accelerated rehabilitation decreased disability, depression, and pain; increased functionality; and improved quality of life. In the process of returning to sport, specific criteria, rather than timeline-based progression, should be used.…”
Section: Accelerated Approachmentioning
confidence: 99%